TRAINING, PROFESSIONAL COMPETENCE AND EMPLOYEE PERFORMANCE: TESTING A PROPOSED MODEL - Ardi, Rudi Prasetyo; Udin, Udin; Wahyudi, Sugeng; Akbar, Abu Bakar; Perdhana, Mirwan Surya; Anggraeni, Ngurah Ayu Dian (International Journal of Psychosocial Rehabilitation, 2020)
Organizations face increasingly fierce competition due to globalization, changes in technology, politics, and economics. The purpose of this study is to examine the effect of training on professional competence and employee performance. 143 respondents who worked at building construction companies in Central Java - Indonesia are determined as samples. The results of the study using SmartPLS 3 reveal that training has a significant effect on professional competence and employee performance. Besides, professional competence also significantly affects employee performance.